Antibacterial Activity of Melaleuca alternifolia Extract from Different Extraction Method - Husnul Khotimah Matoha; Fitriana Fitriana; Yuli Widiyastuti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Melaleuca alternifolia (Tea tree/MA) is a powerful antimicrobial agent that could be one of the solutions to antimicrobial resistance. The important benefit of this plant comes from its volatile oil compounds named tea tree oil (TTO). On the other hand, studies related to the use of tea tree leaf extract as antimicrobial were still limited. Therefore, an evaluation of the active compound content and antimicrobial activity of tea tree extract obtained from different extraction methods will be carried out. Thin-layer chromatography (TLC) was performed to analysis the chemical profile, the antibacterial activity of the extracts was evaluated using the Kirby Bauer method against Staphylococcus aureus and Escherichia coli, whereas the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) was determined by broth dilution method. Based on the chromatographic profile of the extract indicated that cardiac glycosides and terpenoids could be present in maceration and soxhletation extracts. This study suggests that maceration and soxhletation yielded different bioactive compounds from MA. Extracts of MA from both method have an excellent activity to inhibit the S. aureus, and E. coli in a dose-dependent manner. Maceration extract of MA has a stronger effect against E. coli meanwhile the soxhletation extract of MA reveals to have stronger antimicrobial activity against S. aureus. The both extract even obtained from different extraction method yielded the same MIC and MBC values namely = 0.1875% against E. coli. In contrast MBC of S. aureus range from two to fourfold of the MIC, and the maceration seem to have the highest MBC value (MBC = 12%).